Mengevaluasi Tantangan Keamanan dalam Sistem Akses Digital untuk Pendidikan Kejuruan yang Didukung Teknologi: Tinjauan Literatur Sistematis - Kennedy Barfi Yaw Agyeibi; Budi Mulyanti; Agus Setiawan; Lala Septem Riza; Ilhamdaniah Ilhamdaniah (Fakultas Seni Rupa dan Desain ITB, 2026)
The rapid expansion of technology-enabled vocational education has increased reliance on digital access systems that regulate entry to learning platforms, simulations, and assessment environments. This study examines how security challenges in these systems affect learning continuity in vocational education and identifies factors that intensify disruption risks. A systematic review of peer-reviewed studies published between 2020 and 2025 was conducted using five academic databases, applying predefined inclusion criteria and synthesizing findings through descriptive and thematic analysis. Results show that weaknesses in data confidentiality, integrity, and especially system availability frequently interrupt instructional activities, particularly practice-based learning dependent on digital laboratories and assessment tools. Disruptions are often amplified by misalignment between technical infrastructure, user practices, and institutional governance, with institutions lacking governance capacity and user training facing higher risks of learning interruption. Although technical and administrative mitigation strategies exist, they are often implemented without sufficient alignment to pedagogical needs. The study concludes that digital access security should be treated not merely as a technical concern but as a prerequisite for equitable and resilient vocational learning, calling for integrated socio-technical and pedagogically informed security strategies.